Bioinspired materials and tissue engineering approaches applied to the regeneration of musculoskeletal tissues - Rodrigues, Márcia T. (2020)
The musculoskeletal tissues have a prime role in the biomechanical support and metabolic activities of the human body. As musculoskeletal tissues are highly prone to injuries, conditions afflicting these tissues have a great impact on the quality of life of patients worldwide. Tissue engineering approaches hold the promise to develop bioengineered substitutes aiming at the regeneration of failing and injured tissue and organs. To effectively address the tissue-specific structural and biochemical features of musculoskeletal tissues, different biomaterials and techniques have been employed envisioning biomimetic solutions. Herein, the unique composition, structure, and function of the musculoskeletal tissues, namely bone, cartilage, and tendon, as well as state-of-the-art technologies to develop bioinspired strategies for tissue regeneration will be overviewed. Finally, this chapter will also discuss the unmet challenges and future perspectives in the field.